The Effect of Liquidity, Solvency, Activity, and Profitability, on Company Value: Pharmaceutical and Food & Beverage (2020-2022) - Sal Sabila, Asa Aisyi; Diana, Nur; Sudaryanti, Dwiyani (Universitas Islam Malang, 2024)
Company value is a crucial element in the company's attractiveness to investors, because investors are generally interested in investing in companies that have high firm value, so they can get optimal returns. This study aims to analyze the influence of Liquidity, Solvency, Activity, and Profitability on Company Value: Pharmaceuticals and Food & Beverages listed on the Indonesia Stock Exchange (IDX) during the period 2020-2022. This research utilizes secondary data obtained through documentation techniques, namely by collecting information from financial statements announced on the Indonesia Stock Exchange during the specified period and from literature sources. Data was analyzed using multiple linear regression methods and processed using SPSS Version 27. The results of this study explain that simultaneously liquidity, solvency, activity and profitability have no simultaneous effect on firm value. The results show that profitability significantly affects company value, while liquidity, solvency, and activity do not significantly affect it. The benefits of this research are practical for the company, this research is expected to contribute to the optimization of company value. For investor, contribute ideas or literacy for investors to conduct studies and knowledge about the valuation of companies to be funded.Keywords: Liquidity, solvency, activity, profitability, company value